IMPLEMENTASI PENDIDIKAN ORGANISASI HMI (HIMPUNAN MAHASISWA ISLAM) DALAM MEWUJUDKAN MAHASISWA YANG INOVATIF DAN BERAKHLAK DI KOMISARIAT FAKULTAS ILMU SOSIAL UIN SUMATERA UTARA - M. Ali Akbar Siregar; Sori Monang (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The development of the internet has had a major impact on moral behavior, many generations are easily influenced by negative behavior in their social environment, Indonesia's moral generation in modern times faces many significant challenges. In line with this, it is hoped that the HMI organization will produce innovative and moral students within the commissariat of the Faculty of Social Sciences, UIN North Sumatra. The aims of this research are: (1) To determine the Implementation of Innovative and Moral Education Organizations; (2) Bringing Up Factors Supporting and Hindering the Implementation of Innovative and Moral Organizational Education; and (3) Assessing the Impact of Implementing Innovative and Moral Education Organizations. This research uses qualitative research with data collection techniques such as interviews, observation, and documentation. While data analysis uses the Miles and Huberman methodology, it also includes data reduction, data presentation, and conclusions. Based on the findings of research conducted by the research organization HMI Commissariat of the Faculty of Social Sciences, it can be concluded that (1) Implementation of innovative and moral organizational education, namely admonishing fellow members, politeness in speaking, time discipline, mutual respect internally and externally (2) Factors supporters in the implementation of innovative and ethical organizational education, namely interest, sincerity, loyalty in realizing HMI organizations in realizing innovative and ethical students. And the inhibiting factors for the implementation of the HMI organization in realizing innovative and moral students at the Faculty of Social Sciences Commissariat are inconsistent student attendance and different student characteristics.